KNOWLEDGE RATHER THAN LANGUAGE PROFICIENCY AFFECTS ACHIEVEMENT SCORES IN INTERACTIVE OBJECTIVELY STRUCTURED PERFORMANCE EVALUATION - Khan, Junaid Sarfraz; Tabasum, Saima; Shah, Syed Jawad Ali (Journal of Ayub Medical College Abbottabad, 2009)
Background: A common belief is that language proficiency might have affected the outcome scores of the Oral Structured Performance Evaluation (OSPE) especially at the interactive stations. The objective of this study was to explore this postulation. Methods: The subject of Behavioural Sciences was examined for the first time as a component of undergraduate medical curriculum in 2nd Professional Medical Examinations in 2007. Equal weightage was given to written and OSPE components in the examination. The OSPE scores in the interactive component of all (1457) candidates were compared with their written scores in the subject of Behavioural Sciences as well as their Higher Secondary School Certificate (HSSC) scores in the subject of English using Multiple Linear Regression Analysis in SPSS v.12. Results: Overall as well as in the Public Medical Colleges, relative to each other, knowledge of the subject as indicated by marks obtained in the written component of the examination exerted a positive and statistically significant (p<0.05), and command over language as indicated by marks obtained in the HSSC examination exerted a small positive but statistically insignificant (p=0.231 and 0.639 respectively) influence on the performance of students in the interactive OSPE component. In the private medical colleges command over language exerted a small negative but statistically insignificant (p=0.936) influence on the performance of students in the interactive OSPE component of the examination. Conclusion: Command over the subject content is the best indicator of achievement in OSPE. Keywords: Objectively Structured Performance Evaluation, OSPE, Language Proficiency, Behavioural Sciences